MCSD training guide : microsoft access - Dulaney, Emmett; Graven, Sheila; Jones, Angela J.R.; Loy, Stephen P. (Indianapolis, IN : New riders pub., 1997)
This text should provide the reader with the information needed to pass this exam. Combining the real-life knowledge of professionals with the expertise of MCSEs and MCSDs, the book contains insider tips and notes on passing the MCSD exam.
Includes index.
Keywords: Electronic data processing personnel -- Certification; Microsoft software -- Examinations -- Study guides; Microsoft Access